Informatics Transformation of Traditional Indian Herbs into Phytopharmaceuticals: Process Modelling and Optimization (Journal of Informatics Education and Research, 2026)
Throughout the globe, plant-derived drugs have been (and continue to be) a longstanding pillar of therapeutic medicine, finding themselves to be an integral part in drug research in primary health care. The lack of standardisation and uniformity, as well as safety and batch-to-batch variability (causing the issue of consistent reproducibility at a large scale) in the production of phytopharmaceuticals are crucial issues that require to be addressed to increase the adoption of herbal medicines in the modern world (Naik et al., 2023). To maintain uniformity and safety, regulatory aspects (such as toxicological concerns, interaction issues and storage issues) also need to be addressed. One means of doing this is by a constant and rigorous monitoring of adverse reactions caused by newly formulated herbal pharmaceuticals (Naik et al., 2023). Traditional plant-derived medicines in India have been found to hold a substantial number of bioactive compounds. Despite this, their acceptance into the global market remains low due to issues such as batch-to-batch variability and little regulatory compliance (as aforementioned). Hence, a standardised approach to align traditional herbal knowledge with modern day extraction, purification and formulation science aligned with a chemical engineered blueprint must be brought about to reduce the issue of scalability and reproducibility in multiple environments, complying with a regulated framework to develop phytopharmaceuticals. Connecting ethnomedicinal research to industrial pharmaceutical manufacturing is a barrier that remains to be overcome; to do so, embedding QbD, PAT and eco-friendly green engineering principals into the development of these drugs. A qualitative research methodology was used, putting together a systematic review of peer-reviewed literature from Scopus, PubMed, and IEEE Xplore with qualitative multiple case study analysis of Indian phytopharmaceutical manufacturers. Cross-case synthesis was used to identify convergent patterns in extraction efficiency, formulation stability, process control, and environmental performance. The resulting findings showcased that eco-friendly/green engineering technology such as supercritical fluid extraction and hybrid membrane purification in order to extract bioactive significantly improved purity and increased yield. An incorporation of formulation strategies from the field of material sciences have also been found to improve the solubility and stability of herbal pharmaceuticals, nanoencapsulation and engineered excipient systems being the prime examples. Implementing a framework that puts forward the regulatory readiness by changing the safety and quality control aspects of development from post-production testing to testing necessary material during the in-process stage is imperative.